Impacts of an early education intervention on students' learning achievement: Evidence from the Philippines - Yamauchi, Futoshi; Liu, Yanyan (International Food Policy Research Institute, 2011)
This paper examines the impact of a large supply-side education intervention in the Philippines, the Third Elementary Education Project, on students' national achievement test scores. We find that the program significantly increased student test scores at grades 4 to 6. The estimate indicates that the six-year exposure to the program increases test scores by about 15 score points. Interestingly, the mathematics score is more responsive to this education reform than other subjects. We also find that textbooks, instructional training of teachers, and new classroom constructions particularly contributed to these outcomes. The empirical results also imply that early-stage investments improve student performance at later stages in the elementary school cycle, which suggests that social returns to such an investment are greater than what the current study demonstrates.